La escritura telérgica - Luciana Martínez (Cuadernos LIRICO)
“The telergic writing” proposes an analysis of Levrero´s early work from the concept of “telergy” which appeared in his Manual of Parapsychology (Manual de Parapsicología, 1979). In previous essays it was stated that late levrerian fictions try to accomplish a “mancy” function (concept included in the Manual as well) to attain an approach to an ideal self as well as to different forms of the Absolute. Herein, it is proposed that in early texts from the Uruguayan author the search for an ideal identity is carried out through a presentation of different kinds of characters who are not but incomplete or partial versions of the protagonist-self. Telergy functions in this last sense as a concept that explains certain inflections of early levrerian narrative, like the double-type, from the universe of the Manual. Related to the identity problem, crucial in Levrero, other concepts present in his fictions such as the “cobweb”, the “labyrinth” and the “trap” are also analyzed. In a general way, such concepts emerge from fictions that seek to overcome (but always fail) an outside.